Use of Coronary Artery Calcium Scanning Beyond Coronary Computed Tomographic Angiography in the Emergency Department Evaluation for Acute Chest Pain. (March 2015) - Pursnani, Amit; Chou, Eric T.; Zakroysky, Pearl; Deaño, Roderick C.; Mamuya, Wilfred S.; Woodard, Pamela K.; Nagurney, John T.; Fleg, Jerome L.; Lee, Hang; Schoenfeld, David; Udelson, James E.; Hoffmann, Udo; et al.
<x xml:space="preserve">Abstract</x> Background— Whether a coronary artery calcium (CAC) scan provides added value to coronary computed tomographic angiography (CCTA) in emergency department patients with acute chest pain remains unsettled. We sought to determine the value of CAC scan in patients with acute chest pain undergoing CCTA. Methods and Results— In the multicenter Rule Out Myocardial Infarction using Computer-Assisted Tomography (ROMICAT) II trial, we enrolled low-intermediate risk emergency department patients with symptoms suggesting acute coronary syndrome (ACS). In this prespecified subanalysis of 473 patients (54±8 years, 53% men) who underwent both CAC scanning and CCTA, the ACS rate was 8%. Overall, 53% of patients had CAC=0 of whom 2 (0.8%) developed ACS, whereas 7% had CAC>400 with 49% whom developed ACS. C-statistic of CAC>0 was 0.76, whereas that using the optimal cut point of CAC≥22 was 0.81. Continuous CAC score had lower discriminatory capacity than CCTA (c-statistic, 0.86 versus 0.92; P=0.03). Compared with CCTA alone, there was no benefit combining CAC score with CCTA (c-statistic, 0.93; P=0.88) or with selective CCTA strategies after initial CAC>0 or optimal cut point CAC≥22 (P≥0.09). Mean radiation dose from CAC acquisition was 1.4±0.7 mSv. Higher CAC scores resulted in more nondiagnostic CCTA studies although the majority remained interpretable. Conclusions— In emergency department patients with acute chest pain, CAC score does not provide incremental value beyond CCTA for ACS diagnosis. CAC=0 does not exclude ACS, nor a high CAC score preclude interpretation of CCTA in most patients. Thus, CAC results should not influence the decision to proceed with CCTA, and the decision to perform a CAC scan should be balanced with the additional radiation exposure required. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01084239.